Genetic Causes of Generalized Epilepsies - Helbig, Ingo (Seminars in Neurology, 2015)
Generalized epilepsies, particularly the idiopathic or genetic generalized epilepsies (GGEs), represent some of the most common epilepsies. Clinical genetic data including family studies and twin studies provide compelling evidence for a prominent genetic impact. The first decade of the 21st century was marked by progress in understanding the basic biology of generalized epilepsies including generalized/genetic epilepsies with febrile seizures plus (GEFS+) and GGE through studies of large families, discovering causative mutations in SCN1A, SCN1B, GABRG2, and GABRA1. Subsequently, recurrent microdeletions at 15q13.3, 16p13.11, and 15q11.2 were found to be relevant risk factors for nonfamilial GGE. Genes for epileptic encephalopathies such as SLC2A1 were rediscovered in GGE, highlighting the biological continuum between different epilepsies. Genome-wide studies examining common genetic risk factors identified common variants in SCN1A, indicating a convergence of shared pathophysiological pathways in various types of epilepsies. In the era of next-generation sequencing, however, the GGEs appear more complex than expected, and small or moderately sized studies give only a limited genetic perspective. Thus, there is a strong impetus for large collaborative investigations on an international level.
Keywords: genetic generalized epilepsy; copy number variation; exome sequencing